2020
DOI: 10.1002/hed.26467
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic potential of mid‐treatment nodal response in oropharyngeal squamous cell carcinoma

Abstract: Background: We examine the prognostic implications of mid-course nodal response in oropharyngeal cancer (OPX) to radiation therapy. Methods: In 44 patients with node-positive OPX undergoing concurrent chemoradiation, nodal volumes were measured on cone beam CTs from days 1, 10, 20, and 35. Nodal decrease (ND) was based on percent shrinkage from day 1. Results: At a median follow-up of 17 months, the 2-year disease-free survival (DFS), locoregional control (LRC), distant metastasis-free survival (DMFS), and ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The survival data for these two strata were compared using the log rank statistical test to test the null hypothesis that there is no difference between the survival curves, and this test yielded a p-value of 0.01. This stratification is in line with the prognostic value of mid-treatment nodal response observed by other groups [19]. The definition of these strata enables the relation of tumor volume changes and estimated personalized RT dose with patient outcomes.…”
Section: Patient Datasupporting
confidence: 72%
“…The survival data for these two strata were compared using the log rank statistical test to test the null hypothesis that there is no difference between the survival curves, and this test yielded a p-value of 0.01. This stratification is in line with the prognostic value of mid-treatment nodal response observed by other groups [19]. The definition of these strata enables the relation of tumor volume changes and estimated personalized RT dose with patient outcomes.…”
Section: Patient Datasupporting
confidence: 72%
“…In head and neck cancer, mid-treatment volumetric responses correlate with outcome ( 31 , 47 ). Patients with greater than 32.2% tumor volume reduction after 4 weeks of RT were 100% locoregionally controlled (LRC) at a mean follow-up time of 20 months.…”
Section: Methodsmentioning
confidence: 99%
“…A study from New York University showed that patients who had low-risk OPC with ≥43% nodal decrease on cone-beam CT by treatment day 20 had superior 2-year LRC. 130 Consequently, in their trial (ClinicalTrials.gov identifier NCT03215719; Table 9), interval scans at 4 weeks will be the in-silico trial of dynamics-adapted dose personalization estimated that 77% of patients treated with SOC 66-70 Gy were overdosed by an average of 39 Gy. 133 Even further beyond this mathematical model predicting that a majority of patients may only need approximately 30 Gy was the most drastic dose de-escalation trial to date, which delivered 30 Gy to the majority of patients: the 30 ROC trial from Memorial Sloan Kettering Cancer Center.…”
Section: Radiomics and Functional Imagingmentioning
confidence: 99%
“…Another approach harnesses radiomics using intratreatment imaging to identify early responders. A study from New York University showed that patients who had low‐risk OPC with ≥43% nodal decrease on cone‐beam CT by treatment day 20 had superior 2‐year LRC 130 . Consequently, in their trial (ClinicalTrials.gov identifier NCT03215719; Table 9), interval scans at 4 weeks will be used to identify responders and adaptively de‐escalate to 60 Gy in patients who have >40% nodal shrinkage.…”
Section: The Future Of De‐escalation: Intratreatment Response Assessm...mentioning
confidence: 99%